Electrolysis of Seawater for Hydrogen Production: Influence Voltage and Electrode Types - Aqbal Ali Abbas; Ali Kamel Mohsin (Genius Journals, 2023)
In fact, fossil fuels cause carbon dioxide (CO2) pollution in the atmosphere and causing global warming. Thus, environment needs to be clean from these pollutions. Renewable energy that environmentally friendly are needed, which is hydrogen gas considered capable of being an alternative to replace the fossil fuels. Electrolysis is one of many ways to produce hydrogen gas. In this study, the seawater has been selected because of its abundant availability. It has high efficiency and low cost to produce the gas. To varying the voltage from 2 volts to 22 volts with an increase of 1.5 volts, the aim of this research was to investigate the impact of the different voltage on rate of hydrogen and the level of production through electrolysis of seawater with estimate time 10 mins time. Copper and graphite electrode have been used in this research. The results have been showed that the productivity coefficient of copper has been recorded 0.41 ml with 0.97 determination coefficient, however, graphite electrodes has been recorded 0.32 ml with determination coefficient of 0.93. The study has been also reported that the maximum of level hydrogen gas was 8.5 ml. it has produced through the electrolysis of seawater that using copper at a voltage of 21 volts. However, graphite electrodes produced a maximum level of hydrogen gas was 9.7 ml at a voltage of 25 volts.
Keywords: Electrolysis; Hydrogen; Metal electrodes